Scientific Theories on the Origin of Mahdist Beliefs - Mustafayev, Elnur (Scholarya Demo Journal of Ruby, 2020)
This article explores the origins of Mahdhist beliefs and its reasons. Man instinctively awaits a savior in times of political and economic difficulties caused by natural disasters, cataclysms and wars, and this fact is one of the most pressing problems for religions. Mahdism is one of the common beliefs for all religions as the belief in saviors can be seen in most them. It should be noted that faith in the Mahdi is superficial in several religions and ideological movements; however, it is strong in some religions. Mahdist beliefs became one of the basic principles of a number of religions and proved to be a source of energy for these religions. Obviously, the religious approach to the idea of savior is ambiguous and there are common features and differences. Issues such as the identity and characteristics of the savior who will save the world are different depending on religion. The article compares and analyzes the scientific approaches of European scholars and theologians who conducted research on the origin of the faith in salvation. In addition, such nuances as the psychological, psychosocial and political reasons for the belief in the Mahdi have been studied.